Analysis of land cover change in Magelang Regency And Magelang City over 15 years - Nasir, Muhammad Nurhalik (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Land cover change is an ongoing phenomenon with significant impacts on the environment and human quality of life. An analysis of land cover change was conducted in the Magelang area, which includes both Magelang Regency and Magelang City, over a period of fifteen years from 2007 to 2023. This study aims to analyze these changes using spatial methods based on land cover maps from 2007 and 2023. Method: In this analysis, land cover was classified into five categories: settlements, dry fields, paddy fields, forests, and plantations, and then compared between the two years. Result: The analysis results demonstrate a significant increase in the area of settlements and dry fields, reflecting urban and rural development. On the other hand, there has been a decrease in the area of paddy fields and forests, which may be related to land conversion for industrial or infrastructure purposes. The change in the area of plantations was not significant, indicating continuity in the management of these lands. Conclusion: The findings of this study provide valuable insights into the dynamics of land cover change in the region and can serve as a basis for further actions to maintain a balance between development and environmental conservation. Novelty/Originality of this study: This study presents the first longitudinal spatial analysis of land cover changes over 15 years (2007–2023), revealing significant trends in urban and rural land use dynamics. This study provides a scientific basis for sustainable spatial planning by highlighting the urgency to balance development infrastructure with preserving farmland and forests.